1997
DOI: 10.1073/pnas.94.9.4504
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a fucosidase from a galactosidase by DNA shuffling and screening

Abstract: An efficient ␤-fucosidase was evolved by DNA shuff ling from the Escherichia coli lacZ ␤-galactosidase. Seven rounds of DNA shuff ling and colony screening on chromogenic fucose substrates were performed, using 10,000 colonies per round. Compared with native ␤-galactosidase, the evolved enzyme purified from cells from the final round showed a 1,000-fold increased substrate specificity for onitrophenyl fucopyranoside versus o-nitrophenyl galactopyranoside and a 300-fold increased substrate specificity for p-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(85 citation statements)
references
References 28 publications
1
83
0
1
Order By: Relevance
“…The authors estimate that mutating the same number of positions as are changed in a recombination event among these proteins would abolish protein function (Chang et al 1999). Such weak deleterious effects may contribute to the promise recombination shows in engineering new proteins (Stemmer 1994;Crameri et al 1997Crameri et al , 1998Zhang et al 1997;Chang et al 1999;Kolkman and Stemmer 2001;Leong et al 2003;Raillard et al 2001a,b). Because recombination can reorganize genetic systems on a much larger scale than point mutations, these weak effects on different levels of organization are intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…The authors estimate that mutating the same number of positions as are changed in a recombination event among these proteins would abolish protein function (Chang et al 1999). Such weak deleterious effects may contribute to the promise recombination shows in engineering new proteins (Stemmer 1994;Crameri et al 1997Crameri et al , 1998Zhang et al 1997;Chang et al 1999;Kolkman and Stemmer 2001;Leong et al 2003;Raillard et al 2001a,b). Because recombination can reorganize genetic systems on a much larger scale than point mutations, these weak effects on different levels of organization are intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Chromogenic substrates have been used successfully in a number of studies utilizing a 96-well plate reader or visual screening of the colored colonies (48,49). With VAO, the end product vanillin formed upon the two-step oxidation of creosol could be measured directly in whole cells by absorption spectroscopy at 340 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Although simple DNA base substitutions are well suited for the generation, diversification, and optimization of local protein space (Maeshiro and Kimura 1998), a hierarchy of natural mutational events is required for the rapid generation of protein diversity. Experimental evolution (Moore et al 1997;Zhang et al 1997;Crameri et al 1998) and computer simulation experiments (Bogarad and Deem 1999) showed that sequence shuffling has the potential to improve protein function significantly better than does point mutation alone. Because they are uniquely competent to reshuffle DNA sequences, TEs and viruses are important generators of the more complex types of mutations in the mutational hierarchy.…”
Section: Broad-spectrum Mutator Mechanismsmentioning
confidence: 99%